Un Primer apropament al santoral de la consueta RC. 0031 (Olim Roda 13) de l'Arxiu Capitular de Lleida del segle XV - Fité Llevot, Francesc (Miscel·lània litúrgica catalana, 2016)
As stated in the title, this study aims to be an initial approach to the Calendar of the Consuetudinary RC.0031, from Roda dIsàvena, preserved in the Arxiu Capitular de Lleida (Lleidas Capitular Archive, ACL). In it, we first establish the chronology of the manuscript around the opening decades of the 15th century and then we look at its features, taking this opportunity to offer a full transcript of the Regulae. We then turn to the Calendar, which we compare with other manuscripts of the ancient cathedral, in particular, the Calendar of the Breviary (ACL, LC.0016)of 1451, and the Calendar in the Lectionary from the 14th century (ACL, RC.0026). Lastly, we devote a section to the Marian cult and especially to the seasonal liturgy, with mention of the liturgical dramas that were held at the Cathedral of Lleida.